Unequal access to protection? Selection patterns over arrival cohorts of Syrians seeking refuge in Lebanon, Turkey, and Germany - Gundacker, Lidwina; Keita, Sekou; Ruhnke, Simon A. (Frontiers in Human Dynamics, 2024)
An ample scholarly literature on voluntary migration has shown that migration is a highly selective process, resulting in migrant populations that often differ significantly from their respective population of origin in terms of their socio-demographic characteristics. The literature attributes these differences to either migrants' active choice and agency in the migration decision (i.e., self-selection), or to selectively applied external constraints. Although the socio-demographic make-up of forced migrant populations has received significant attention in public discourses in receiving countries such as Germany and Turkey, the literature on migrant selection largely focuses on voluntary migration and self-selection mechanisms. As a result, the selection mechanisms of forcibly displaced persons are less well understood. In this study we contribute to that literature by investigating differences in forced migrant selection outcomes in countries of first refuge neighboring the origin country, relative to a reception country in the global north. Based on novel household survey data, we compare age, gender, socio-economic background and family context of the Syrian populations in Lebanon, Turkey, and Germany by arrival cohort (2013-2017). We furthermore explore two potential selection mechanisms of forced migrant populations. Particularly in the context of forced migration, the conditions for migration fluctuate heavily within a relatively short time span, e.g. regarding immigration policies and border controls. We explore the changing conditions under which Syrians sought international humanitarian protection and link them to the selection outcomes in the three destination countries. In a narrative approach, we establish legal and political frameworks as well as the accessibility of routes as external barriers to forced migration. We combine the cohort analysis of Syrians in Lebanon, Turkey, and Germany with contextual analyses of the (changing) frameworks governing refugee migration in transit and destination countries and descriptive analyses of changing risk levels along routes. Our analyses reveal that higher external barriers coincide with a stronger selection in migrants’ socio-demographic make-up. In particular, riskier routes and higher entry barriers are associated with a lower share of female migrants, a lower share traveling with family members, and a higher socio-economic background.